Role of Novel Drug Delivery Vehicles in Nanobiomedicine 2020
DOI: 10.5772/intechopen.84424
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Properties: Functionalization and Surface Modified Nanoparticles

Abstract: Herein, the various polymer properties and the underlying mechanism for the functionalization and surface modification of polymer nanoparticles have been discussed. There are numerous polymer particles designed and developed for various applications. The synthesis and characterization of different types of polymers followed by the engineering of nanoparticles and capsules depend on various factors. There are too many polymerization methods approached for the development of nanoparticles with desired surface pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 77 publications
0
17
0
Order By: Relevance
“…Moreover, for the interaction between BAC molecules and bacteria to occur, the particles need to be in close contact with bacteria. Of course, the BAC molecules inside the pores will not be readily available for bacteria [ 62 ], since the particles are mesoporous (pore diameters between 2 and 50 nm [ 63 ]) and bacteria (due to their bigger size) cannot enter the pores. In the work of He et al [ 56 ], they found that bacteria are dead upon contact with the immobilized QACs.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, for the interaction between BAC molecules and bacteria to occur, the particles need to be in close contact with bacteria. Of course, the BAC molecules inside the pores will not be readily available for bacteria [ 62 ], since the particles are mesoporous (pore diameters between 2 and 50 nm [ 63 ]) and bacteria (due to their bigger size) cannot enter the pores. In the work of He et al [ 56 ], they found that bacteria are dead upon contact with the immobilized QACs.…”
Section: Resultsmentioning
confidence: 99%
“…In most of the techniques requiring the use of preformed polymers, organic solvents are commonly used in the first step to dissolve the polymer [28]. These solvents can generate problems related to toxicity and environmental risk.…”
Section: Methods For Production Of Polymeric Nanoparticlesmentioning
confidence: 99%
“…Depending on the type of drug to be loaded in the polymeric NPs and their requirements for a particular administration route, different methods can be used for the production of the particles [ 26 ]. In general, two main strategies are employed, namely, the dispersion of preformed polymers or the polymerization of monomers [ 27 , 28 ]. Table 2 lists the most commonly used techniques [ 29 , 30 ].…”
Section: Methods For Production Of Polymeric Nanoparticlesmentioning
confidence: 99%
“…In active targeting, the surface of nanocarriers is modified to generate affinity with bioreceptors or cellular biomarkers, tissues or organs through ligand-receptor interactions [ 46 , 53 ]. Ligand-nanocarrier conjugation uses different coupling methodologies, including the formation of disulfide bonds, cross-linking, covalent coupling, ionic interactions, layer-by-layer assembly, among other strategies [ 54 ]. Coating the nanocarriers with targeting ligands such as peptides, antibodies, lectins, sugars, folate- and mannose-receptors, among others, drive them to the site of action, thereby increasing the concentration of the active principle in the place and avoiding non-specific accumulations and the concomitant adverse effects [ 55 , 56 , 57 ].…”
Section: Polymeric Nanocarriers Against Intracellular Infections: mentioning
confidence: 99%